DOES CORPORATE GOVERNANCE MODERATE THE EFFECT OF RELATED PARTY TRANSACTIONS ON REAL EARNINGS MANAGEMENT? - Hapsoro, Dody; Hendrik, Dhenayu Tresnadya (Jurnal Akuntansi, 2023)
This study aims to examine the ability of corporate governance in moderating the effect of related party transactions on real earnings management. The institutional ownership and financial expertise of the audit committee are used as a proxy for measuring corporate governance. This study uses a purposive sampling technique in manufacturing companies listed on the Indonesia Stock Exchange. The study period began from 2018 to 2022. The results showed that related party transactions had a positive and significant effect on real earnings management. Furthermore, institutional ownership is able to moderate the effect of related party transactions on real earnings management and the financial expertise of the audit committee is not able to moderate the effect of related party transactions on real earnings management.